Pembinaan Al-akhlāq al-Karīmah melalui Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Atas Kabupaten Probolinggo, Jawa Timur, Indonesia - Hendi Sugianto; Mawardi Djamaluddin (DAYAH: Journal of Islamic Education, 2021)
This paper discusses noble character instilment through Islamic education in SMA Tunas Luhur, Paiton, Probolinggo. It employs field research by using references related to the discussed topic. It argues that the instillment of noble character through Islamic Education in SMA Tunas Luhur, Paiton, Probolinggo implies the teachings of noble character to God, human beings, and the environment. Besides, it increases the learners' piety to Allah and their academic achievement. The moral instilment to God is implemented through praying Duha, Dhuhr, and Asr in the congregation at the school and in-chain phone calling to wake up the students in the early morning to pray Tahajjud. The instilment of morals to human beings is made through qur'anic gathering, social service, and granting compensation to orphans and the poor. Meanwhile, the instilment of morals to the environment is implemented through good deeds, such as preserving the environment. This school's program is successful for the students' capability to implement the right behaviors to either God, human beings, or the environment in their everyday life.